Implementasi Sistem-informasi Desa Berbasis Arsitektur Microservices - suryo atmojo; Ruli Utami; Suzana Dewi; Nurwahyudi Widhiyanta (LPPM UBHINUS MALANG, 2022)
Information systems can be said to be good, namely, the system can provide convenience in presenting information, must also be able to survive when experiencing disturbances, and be able to adapt. The ability to deal with disturbances and adapt is called resilience. One of the information system architectures that lack resilience capabilities is monolithic architecture, where the backend and frontend systems are combined in the same functions and services, besides that the monolithic architecture also runs all logic in one application server. The microservice architecture allows the development of functions in an application or information system to be broken down into several small service parts and makes the service have the ability to manage resources properly and become a small service that is interconnected into one. The design of this microservice-based Village Information System is the best solution to solve the problems that exist in monolithic architecture-based information systems, especially in village information systems. In this study, the case study focuses on problems in the Pengalangan Village Information System such as rapidly changing system requirements, system requirements that can be easily expanded, accessibility that only depends on one technology, administrative stacks, more files, report generation that requires time because the data collection process is still manual, system security problems for villages that already use information systems, and system development is not easy because they have to overhaul the existing system. By using a microservice architecture, the service performance of village apparatus will increase and become faster, it is easier to expand business processes on the system, and system security is maintained.